Boko haram insurgency in Nigeria: the imperative of institutionalising human rights-based approach to post-contlict peacebuilding in the North-East (2020)
The Boko Haram insurgency in Nigeria has greatly devastated the north-eastern region of the country. Human beings have been killed in the thousands, millions displaced, and the very weak infrastructure hitherto in place completely mangled. The question that looms large in light of the horrendous situation in the north-east is: How can this problem be addressed towards promoting sustainable peace in the region? This is the concern of this paper. Against this background, Parlevliet’s four dimensions of human rights was employed as a framework of analysis for the interrogation of the conflict’s context and the framing of the discussion on the strategies that can be employed to promote sustainable peace in the region. It finds that the root cause of the violent conflict is prolonged human rights violations and abuse at both the vertical and horizontal levels of the society, respectively. The paper concludes that the key to the enthronement of sustainable peace in north-east Nigeria is a post-conflict peacebuilding process that is anchored on the institutionalisation of respect for human rights, especially at the levels of governance and social relations.